The Yb Body, a Major Site for Piwi-associated RNA Biogenesis and a Gateway for Piwi Expression and Transport to the Nucleus in Somatic Cells. - Qi, H.; Watanabe, T.; Ku, H.Y.; Liu, N.; Zhong, M.; Lin, H. (Journal of Biological Chemistry, 2011)
Despite exciting progress in understanding the Piwi-interacting RNA (piRNA) pathway in the germ line, less is known about this pathway in somatic cells. We showed previously that Piwi, a key component of the piRNA pathway in Drosophila, is regulated in somatic cells by Yb, a novel protein containing an RNA helicase-like motif and a Tudor-like domain. Yb is specifically expressed in gonadal somatic cells and regulates piwi in somatic niche cells to control germ line and somatic stem cell self-renewal. However, the molecular basis of the regulation remains elusive. Here, we report that Yb recruits Armitage (Armi), a putative RNA helicase involved in the piRNA pathway, to the Yb body, a cytoplasmic sphere to which Yb is exclusively localized. Moreover, co-immunoprecipitation experiments show that Yb forms a complex with Armi. In Yb mutants, Armi is dispersed throughout the cytoplasm, and Piwi fails to enter the nucleus and is rarely detectable in the cytoplasm. Furthermore, somatic piRNAs are drastically diminished, and soma-expressing transposons are desilenced. These observations indicate a crucial role of Yb and the Yb body in piRNA biogenesis, possibly by regulating the activity of Armi that controls the entry of Piwi into the nucleus for its function. Finally, we discovered putative endo-siRNAs in the flamenco locus and the Yb dependence of their expression. These observations further implicate a role for Yb in transposon silencing via both the piRNA and endo-siRNA pathways.